2009
DOI: 10.4070/kcj.2009.39.9.359
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Alpha-Lipoic Acid on Myocardial Reperfusion Injury: Suppression of Reactive Oxygen Species Generation and Activation of Mitogen-Activated Protein Kinase

Abstract: Background and ObjectivesReactive oxygen species (ROS) and mitogen-activated protein (MAP) kinase play an important role in the development of myocardial reperfusion injury. In this study, we examined whether treatment with alpha-lipoic acid (ALA) before reperfusion could prevent myocardial reperfusion injury in vivo.Materials and MethodsSprague-Dawley rats were subjected to a 45-minute left anterior descending coronary artery ligation followed by 45- or 10-minute reperfusion. ALA was administered 10 minutes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In previous decades, using several different experimental models of I/R, studies have demonstrated the protective effects of LA against I/R-induced injury, including myocardial injury (7), peripheral nerve injury (8), testicular injury (9) and retinal injury (10). In addition, it has been reported that LA can activate phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt and extracellular signal-regulated kinase 1/2 (ERK1/2) pathways to induce protection against I/R injury in other organs (11)(12)(13) to the best of our knowledge, few studies were reported to address whether LA has neuroprotective effects against cerebral I/R-induced injury and its potential mechanisms. In the present study, the neuroprotective effects of LA in rats were investigated with 90 min middle cerebral artery occlusion (MCAO)/24 h reperfusion-induced injury.…”
Section: Introductionmentioning
confidence: 99%
“…In previous decades, using several different experimental models of I/R, studies have demonstrated the protective effects of LA against I/R-induced injury, including myocardial injury (7), peripheral nerve injury (8), testicular injury (9) and retinal injury (10). In addition, it has been reported that LA can activate phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt and extracellular signal-regulated kinase 1/2 (ERK1/2) pathways to induce protection against I/R injury in other organs (11)(12)(13) to the best of our knowledge, few studies were reported to address whether LA has neuroprotective effects against cerebral I/R-induced injury and its potential mechanisms. In the present study, the neuroprotective effects of LA in rats were investigated with 90 min middle cerebral artery occlusion (MCAO)/24 h reperfusion-induced injury.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anti-ROS and anti-RNOS generation involving hypoxic/reoxygenation and peroxidative damage, multiple beneficial effects (e.g., anti-IRI, anti-apoptotic, anti-inflammatory and anti-enzyme effects; fig. 3) have been reported in animal models associated with LA administration [18,19,20,21,22,23,31,32]. These results indicate that LA therapy may serve as a novel treatment modality in clinical setting.…”
Section: Cardioprotection Of Lamentioning
confidence: 61%
“…Pretreatment of rats with schisandrin B (a Chinese herb as an antioxidant) and α-LA recovered the contractile force, inhibited the leakage of lactate dehydrogenase (LDH) and increased myocardial levels of cellular non-enzymatic antioxidants, such as GSH, vitamin C (ascorbic acid) and vitamin E (α-tocopherol) [19]. Pretreatment of myocardial IRI rat model with α-LA also reduced the infarct size, and the effect may be attributed to decreased myocardial apoptosis via suppression of ROS generation and mitogen-activated protein kinase (MAPK) activity (increased activity of pERK1/2 and decreased activity of pJNK1/2) [20]. Administration of LA before reperfusion in rats has shown to protect against myocardial IRI via antioxidant, anti-apoptotic, anti-inflammatory and antioxidant enzyme effects [21].…”
Section: Cardioprotection Of Lamentioning
confidence: 99%
See 1 more Smart Citation
“…tumor necrosis factor-α, intercellular adhesion molecule-1, and monocyte chemoattractant protein-1 [28]. Some experimental studies have demonstrated that ALA restores renal function, limits glomerular mesangial matrix expansion, reduces glomerulosclerosis, and prevents ischemia-reperfusion-induced renal and cardiac injury in animal models [29,30,31,32,33]. …”
Section: Discussionmentioning
confidence: 99%